PENERAPAN MANAJEMEN BANK DALAM TRANSAKSI NON-TUNAI MELALUI PENGGUNAAN QRIS BCA - Ida Ayu Nuh Kartini; Dava Rizqi Al Fajri; Randy Dwi Tinara; Adi Rahmad; Erlangga Rifki Saputra (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The development of digital banking has transformed payment systems, particularly through the implementation of cashless transactions. Banking management plays an important role in ensuring efficiency, service quality, and transaction security in digital payment systems. One of the widely used digital payment instruments in Indonesia is the Quick Response Code Indonesian Standard (QRIS). Bank Central Asia (BCA), as a national private bank, provides QRIS services integrated with mobile banking applications. This community service activity aims to improve public understanding of banking management implementation through the use of QRIS BCA as an object of study. The methods used include socialization, practical assistance, and interactive discussions. The results show an increase in public awareness of operational efficiency, service management, and risk control in cashless transactions. This activity is educational and independent in nature and does not represent the official policy of PT Bank Central Asia Tbk.